Peranan Koperasi Unit Desa Harapan Jaya Terhadap Peningkatan Pendapatan Petani Sawit Di Desa Dak Jaya Kecamatan Binjai Hulu Kabupaten Sintang - B1011141064, Fransiska Fisiarti YUDI ANGGA PRATAMA (Jurnal Curvanomic, 2018)
ABSTRACTThis study aims to analyze the role of the Harapan Jaya Village Cooperative on the level of income of oil palm farmers in Dak Jaya Village, Sintang District. In addition, this study also aims to analyze the operational activities carried out by KUD Harapan Jaya on the level of income of oil palm farmers in Dak Jaya Village, Sintang District.The data used in this study is primary data obtained from the results of answers given by respondents who are members of KUD Harapan Jaya. The results of this study indicate that the existence of KUD Harapan Jaya in an effort to increase farmers' income through its operational activities has been felt quite well by its members who are oil palm farmers in Dak Jaya Village, Sintang District. However, KUD Harapan Jaya is expected to be able to work with the Sintang district government to establish a vocational training center which acts as an institution that provides special training to the community. Other than that KUD Harapan Jaya needs to have workers tasked with overseeing and escorting truck transport from oil palm plantations to the company so that truck drivers do not cheat for personal gain.Keywords : Village Cooperative Unit, oil palm farmers, vocational training centerReferensiÂ Amartya Sen, Stiglitz. 2011. Mengukur Kesejahteraan. Margin Kiri.Anoraga, Pandji, dan Widiyanti, Ninik. 2003. Dinamika Koperasi. Jakarta : PT. Asdi Mahasatya.Arifin, Sitio dan Tamba Halomoan. 2001. Koperasi : Teori dan Praktik. Jakarta : Erlangga.Badrudin, Rudy. 2012. Ekonomika Otonomi Daerah. Yogyakarta : UPP STIM.Baswir, Revrisond. 2000. Koperasi Indonesia, Edisi Pertama. Yogyakarta, BPFE Universitas Gajah MadaBernhard, Limbong. 2012. Pengusaha Koperasi. Jakarta : Margaretha Pustaka.Dewi, N. 2012. Untung Segunung Bertanam Aneka Bawang. Jakarta : Pustaka Baru.Effendi, Rustam dan Widanarko, Agus. 2011. Buku Pintar Kelapa Sawit. Jakarta : PT. Agromedia Pustaka.Hendar, Kusnadi. 2005. Ekonomi Koperasi, Edisi Kedua. Jakarta : Lembaga Penerbit Fakultas Ekonomi Universitas Indonesia.Meyer, B. dan Sullivan, J. 2002. Measuring the Well-Being of the Poor Using Income and Consumption. The Journal of Human Resources.Salikin, K.A. 2003. Sistem Pertanian Berkelanjutan. Yogyakarta : Kanisius.Soekartawi. 1995. Analisis Usahatani. Jakarta : UI Press.Sudarsono dan Edilius. 2002. Koperasi dalam Teori dan Praktek. Jakarta : PT. Rineka.Edi, Susilo. 2013. Peran Koperasi Agribisnis Dalam Ketahanan Pangan di Indonesia. www.ejournal.unisnu.ac.idHertati, Sri Maryati M.Si dan Yolamalinda. Msi. 2011. Peranan Koperasi Unit Desa (KUD) Sungai Aur I Terhadap Peningkatan Pendapatan Petani Sawit di Nagari Sungai Alur Kabupaten Pasaman Barat. Jurnal STKIP-PGRI Sumatera Burat. www.stkip-pgri-sumbar.ac.idSugiarto. 2009. Analisis Tingkat Kesejahteraan Petani Menurut Pola Pendapatan dan Pengeluaran di Perdesaan. Jurnal Pusat Analisis Sosial Ekonomi dan Kebijakan Pertanian. www.pse.litbang.pertanian.go.idSulistyo, Sidik Purnomo dan Brijan Sudjana. 2010. Pemberdayaan Koperasi Unit Desa Melalui Analisis Faktor-Faktor Kunci Manajemen. Jurnal UNPAD. www.jurnal.unpad.ac.idWasilatur, Rohmah, Any Suryantini, dan Slamet Hartono. 2014. Analisis Pendapatan dan Tingkat Kesejahteraan Rumah Tangga Petani Tebu Tanam dan Keprasan di Kabupaten Bantul. Jurnal Universitas Gajah Mada. www.jurnal.ugm.ac.id